2015
DOI: 10.4187/respcare.04250
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pneumothorax Pressures Surpass Higher Threshold in Lung Recruitment Maneuvers: An In Vivo Interventional Study

Abstract: BACKGROUND: Causing pneumothorax is one of the main concerns of lung recruitment maneuvers in pediatric patients, especially newborns. Therefore, these maneuvers are not performed routinely during anesthesia. Our objective was to determine the pressures that cause pneumothorax in healthy newborns by a prospective experimental study of 10 newborn piglets (<48 h old) with healthy lungs under general anesthesia. METHODS: The primary outcome was peak inspiratory pressure (PIP) causing pneumothorax. Animals under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…The occurrence of barotrauma, including pneumomediastinum and pneumothorax, has been reported with the intermittent increase in peak airway inspiratory pressures (10,27,28). In our study, there was no significant difference in the occurrence of pneumothorax between the two groups.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The occurrence of barotrauma, including pneumomediastinum and pneumothorax, has been reported with the intermittent increase in peak airway inspiratory pressures (10,27,28). In our study, there was no significant difference in the occurrence of pneumothorax between the two groups.…”
Section: Discussioncontrasting
confidence: 48%
“…However, lung recruitments using positive pressure have been shown to re-expand collapsed alveoli and improve RV function (23)(24)(25)(26). There is a theoretical risk of developing barotrauma leading to pneumomediastinum or pneumothorax during a recruitment; however this is likely less a risk in cardiac surgical patients with relatively healthy lungs (10,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on the pathophysiology during pneumothorax is outrageously scarce compared with its high incidence [ 20 ]. An experimental study in rats showed that PIP is the only relevant factor that determines pneumothorax [ 21 ]. Briassoulis et al showed that mechanical ventilation produced air leakages, particularly when high peak airway pressures (barotrauma) or large tidal volumes (volutrauma) were delivered by the ventilator [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports the safety of employing recruitment maneuvers in neonatal models [ 15 ]. LRMs have been found to have no deleterious effects on systemic hemodynamics (including arterial blood pressure, central venous pressure, and cardiac output), as well as on respiratory parameters (air trapping and pneumothorax) [ 16 , 17 ]. However, the impact of these maneuvers on cerebral perfusion in neonatal brain models remains unknown.…”
Section: Introductionmentioning
confidence: 99%